Employing group work for task performances in a task-based learning classroom: evidence from a University in Thailand - Ulla, Mark Bedoya; Perales, William F. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Although the pedagogical contributions of cooperative learning to improve the classroom teaching and learning practices have been discussed extensively in the literature, little has been known about the use of group work for task performances in the classroom, especially with regard to the enhancement of English as a foreign language (EFL) students’ speaking performance. The present study reported a classroom teaching practice of a university teacher in Thailand and explored whether group work can positively impact the speaking performances of 106 first-year Thai university EFL students. The course was taught using the group work method in a task-based learning (TBL) framework for 12 weeks. Survey questionnaires and students’ in-class speaking performance scores were used as the data for this study. Findings revealed that although Thai students were new to the group work method, they held a positive attitude towards it. Students believed that performing in-class tasks and activities in groups could help them develop and improve their English language skills as it allowed them to work collaboratively with their classmates. This study adds to the literature on classroom teaching pedagogy, specifically group work and cooperative learning, with implications on materials design.